(untitled) (Global Journal of Computer Science and Technology, 2012)
In this paper, emphasis has been given on the gradual and continuous advancement of computer from on and before 300BC to 2012 and beyond. During this very long period of time, a simple device like computer has witnessed many significant changes in its manufacturing and development. By and large, the changes are conceptual, manufacturing and in ever increasing applications.